1984
DOI: 10.1017/s0031182000054421
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific immunodepression by larval and adult Nematospiroides dubius

Abstract: SUMMARYMice infected with Nematospiroides dubius generate weaker immune responses to concurrently administered sheep red blood cells (SRBC), than non-infected controls. The experiments described in this paper demonstrate that both adult and larval stages of N. dubius cause non-specific immunodepression of the response to SRBC. Mice which had been infected with larvae exposed to 25 krad. of irradiation, which prevents development to the adult luminal stages, produced as weak haemagglutination responses to SRBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Heligmosomoides polygyrus infection takes a far more chronic course than N. brasiliensis or T. spiralis infection. Furthermore, adult H. polygyrus worms in the intestinal lumen seem not to stimulate acquired immunity while inducing immunosuppression (20,21). Although the mechanisms of immunosuppression, as well as Th1 and Th2 responses induced by H. polygyrus infection have not been adequately studied, recent studies showed that H. polygyrus infection in CBA or C57BL/6 mice induces significant decreases in the levels of IL‐17, gamma interferon, tumor necrosis factor alpha, IL‐23, IL‐6 and IL‐1beta while promoting a Th2‐polarized environment in a dual infection model of H. polygyrus and Schistosoma mansoni (34), whereas, other studies have indicated that only mice strains that show a fast response to H. polygyrus (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heligmosomoides polygyrus infection takes a far more chronic course than N. brasiliensis or T. spiralis infection. Furthermore, adult H. polygyrus worms in the intestinal lumen seem not to stimulate acquired immunity while inducing immunosuppression (20,21). Although the mechanisms of immunosuppression, as well as Th1 and Th2 responses induced by H. polygyrus infection have not been adequately studied, recent studies showed that H. polygyrus infection in CBA or C57BL/6 mice induces significant decreases in the levels of IL‐17, gamma interferon, tumor necrosis factor alpha, IL‐23, IL‐6 and IL‐1beta while promoting a Th2‐polarized environment in a dual infection model of H. polygyrus and Schistosoma mansoni (34), whereas, other studies have indicated that only mice strains that show a fast response to H. polygyrus (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike infections with T. spiralis or N. brasiliensis, immunocompetent mice do not exhibit acute rejection of H. polygyrus from the intestine at least until 4 weeks of infection (19). Moreover, adult H. polygyrus worms in the intestinal lumen do not stimulate acquired immunity while inducing immunosuppression (20,21). Therefore, it is of interest to determine whether long‐term nematode infections induce similar intestinal pathology by similar mechanisms to those found in infections with T. spiralis or N. brasiliensis .…”
Section: Introductionmentioning
confidence: 99%
“…How parasites evade immune attack in the tissues has yet to be determined, but it is known that systemic immune suppression is associated not only with the long-lived adult stage but also the larval stage in the intestinal wall [20]. Moreover, mice given curative anthelminthic treatment prior to adult maturation [21], or heavily irradiated infective larvae [22] develop protective immunity to challenge infection.…”
Section: Introductionmentioning
confidence: 99%
“…) of the naturally occurring wood mouse parasite Heligmosomoides polygyrus ). Gastrointestinal nematodes are significant immunomodulators (Ali & Behnke ), often ameliorating immunopathology remote from the site of infection in murine models of autoimmunity (Wilson et al . , ; Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…For experimental studies, we used a laboratory isolate of Heligmosomides bakeri (considered a close relative (Behnke & Harris 2010) or conspecific (Maizels et al 2011) of the naturally occurring wood mouse parasite Heligmosomoides polygyrus). Gastrointestinal nematodes are significant immunomodulators (Ali & Behnke 1984), often ameliorating immunopathology remote from the site of infection in murine models of autoimmunity (Wilson et al 2005(Wilson et al , 2010Liu et al 2009;Hang et al 2010) and co-infection (Furze et al 2006;Bazzone et al 2008), through a dampening of inflammatory responses. In H. bakeri, parasite excretory-secretory products are known to down-regulate TLR function on dendritic cells in vitro (Segura et al 2007).…”
Section: Introductionmentioning
confidence: 99%